Telemedicine - Madhavan, Ramesh; Khalid, Shahram (IntechOpen, 2013)
This book covers original research on the developments within the field of Telemedicine. It is a collection of reviewed scholarly contributions related to Mental health, Internal Medicine, Ophthalmology, Obstetrics and Gynecology, and telemedicine delivery platforms.